Bone Conduction Implants for Hearing Rehabilitation in Skull Base Tumor Patients - Placke, Lauren; Appelbaum, Eric N.; Patel, Akash J.; Sweeney, Alex D. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Bone conduction implants transfer sound to the inner ear through direct vibration of the skull. In patients with skull base tumors and infections, these devices can bypass a dysfunctional ear canal and/or middle ear. Though not all skull base surgery patients opt for bone conduction hearing rehabilitation, a variety of these devices have been developed and marketed over time. This article reviews the evolution and existing state of bone conduction technology.
Keywords: bone conduction implant; skull base surgery; single-sided deafness